THE SEASONAL CYCLE OF SURFACE CHLOROPHYLL ALONG THE PERUVIAN COAST: COMPARISON BETWEEN SEAWIFS SATELLITE OBSERVATIONS AND DYNAMICAL/BIOGEOCHEMICAL COUPLED MODEL SIMULATIONS - Echevin,Vincent (Facultad de Ciencias Naturales y Oceanográficas, Universidad de Concepción, 2004)
The seasonal cycle of surface chlorophyll along the Peruvian coasts is studied with SeaWiFS satellite observations and coupled dynamical/biogeochemical ORCA/PISCES model simulations. The observed mean spatial structure of surface chlorophyll is shown to be in good agreement with that of the model. However the seasonal cycles contrast: whereas the model produces a spring bloom consistent with maximum upwelling and deepest mixed layer in the winter season, the observed seasonal cycle shows two distinct blooms one in late spring-early summer and other in fall. Several hypotheses are suggested to explain the fall bloom and its non-occurrence in the model